Pterygium Pathology: A Prospective Case-Control Study on Tear Film Cytokine Levels - Van Acker, Sara I.; Haagdorens, Michel; Roelant, Ella; Rozema, Jos; Possemiers, Tine; Van Gerwen, Veerle; Tassignon, Marie-José; De Groot, Veva; Ní Dhubhghaill, Sorcha; Koppen, Carina; Zakaria, Nadia (Mediators of Inflammation, 2019)
Pterygium is a common eye disease, linked to an increased exposure to UV radiation and dry environments. The associated pathology culminates in visual impairment and, in some rare cases, blindness. However, there remains a lot of uncertainty concerning the pathogenesis of this fibrovascular lesion. As the composition of the tear film provides a reflection into the pathological changes at the ocular surface, tear analysis represents an ideal approach to gain insight in the progression of disease following pterygiectomy. This study enrolled 19 patients and age/gender-matched healthy controls. Tear film levels of interleukin- (IL-) 6, IL-8, and vascular endothelial growth factor (VEGF) were investigated over time, and preoperative concentrations were linked to corneal neovascularization and pterygium size. Diminished tear film levels were found in unilateral patients who show no clinical signs of pterygium recurrence over a period of one year. Hence, our results highlight the potential of using the course of IL-6, IL-8, and VEGF levels in tears as biomarkers for recovery. In addition, when focusing on the affected eyes (i.e., primary and recurrent pterygium), we detected fold changes in preoperative cytokine concentrations to correspond with disease severity. As our proposed biomarkers did not reveal a linear relationship with corneal neovascularization nor the invasive behaviour of pterygium, no exact role in the pterygium pathology could be established. Hence, our data point to these factors being contributors rather than decisive players in the pathological processes.